Energy–efficient transmissions for bursty traffic in underwater sensor networks. (22nd May 2013) - Chao, Chih–Min; Lu, Ming–Wei
In Underwater Sensor Networks (UWSNs), sensor nodes have limited energy resource and consume a lot of power during message transmission. Since expensive transmitting power consumption is an inevitable feature of underwater acoustic transmission, to extend network operation time, it is desirable for nodes to avoid energy wastage resulting from transmission collisions. Enabling nodes to use multiple channels in a contention–free way helps reduce transmission collisions. To the best of our knowledge, when nodes have bursty traffic loads, existing UWSN multi–channel solutions do not support contention–free transmission while available UWSN single–channel contention–free protocols generally suffer from low utilisation. In this paper, we propose a contention–free multi–channel MAC protocol for UWSNs that work well even when nodes experience uneven and bursty traffic loads. Simulation results verify that the proposed protocol conserves energy and is extremely suitable for a heavy–loaded environment.